EKSTERN ALISME OG INTERN ALISME I ANTROPOLOGIEN - Collin, Finn (Tidsskriftet Antropologi, 1999)
Finn Collin: Externalism and Internalism in Anthropology In anthropology, there is a long-standing debate between intemalists, who insist that anthropology must use the categories of the natives when describing native societies, and extemalists who allow that other and sometimes conflicting categories are permitted. The intemalists derive some support from a contructivist argument to the effect that society is generated by the descriptions that the natives apply to it; hence, it is claimed, the anthropological account must faithfully reflect this description lest native social reality be missed altogether. I argue that this argument is not strong enough to show that anthropological accounts which transcend or even contradict the native ones are always illegitimate. A parallel argument, to the effect that unless he sticks to the natives’ categories, the anthropologist will inevitably commit an ethnocentric injustice in describing native societies in categories that are ultimately derived from his own, is similarly rejected. What emerges is a position that agrees with the intemalists that the point of departure must be taken in the natives’ own self-descriptions, but accepts the extemalists’ point that these categories must subsequently be transcended.